Life satisfaction moderates the associations between motives and excessive social networking site usage. (1st November 2016) - Wang, Jin-Liang; Gaskin, James; Wang, Hai-Zhen; Liu, Dong
Abstract: It has been suggested that excessive social networking sites (SNS) users might use SNS as a method of coping with their life problems and that psychosocial well-being variables might interact with users' motives for using SNS in predicting problematic SNS use. The present research explores whether the association between motives (i.e. self-expression and passing time) and excessive SNS usage is moderated by the user's life satisfaction. A total of 996 college students were recruited from two colleges in Chongqing China. The participants were divided into excessive and nonexcessive SNS usage groups based on their mean score from the excessive SNS usage measurement. Regression analyses revealed that life satisfaction moderates the effect of motives on problematic SNS behaviors among excessive SNS users. Specifically, the motives were significantly related to excessive SNS usage for those with lower life satisfaction, while neither motives were associated with excessive SNS usage in participants with higher life satisfaction. For nonexcessive users, there was no significant interaction between the studied motives and life satisfaction for predicting excessive SNS usage, although the motives were significantly related to the extent of the users' problematic SNS behaviors.